Improving Access to Longitudinal Patient Health Information within an Emergency Department - Wilcox, A.B.; Shen, S.; Dorr, D.A.; Hripcsak, G.; Heermann, L.; Narus, S.P. (Applied Clinical Informatics, 2012)
We designed and implemented an electronic patient tracking system with improved user authentication and patient selection. We then measured access to clinical information from previous clinical encounters before and after implementation of the system. Clinicians accessed longitudinal information for 16% of patient encounters before, and 40% of patient encounters after the intervention, indicating such a system can improve clinician access to information. We also attempted to evaluate the impact of providing this access on inpatient admissions from the emergency department, by comparing the odds of inpatient admission from an emergency department before and after the improved access was made available. Patients were 24% less likely to be admitted after the implementation of improved access. However, there were many potential confounders, based on the inherent pre-post design of the evaluation. Our experience has strong implications for current health information exchange initiatives.
Keywords: Health information exchange; reduced admissions; electronic health records